Health Financing Reform in Ukraine : Progress and Future Directions - Bredenkamp, Caryn; Dale, Elina; Doroshenko, Olena; Dzhygyr, Yuriy; Habicht, Jarno; Hawkins, Loraine; Katsaga, Alexandr; Maynzyuk, Kateryna; Pak, Khrystyna; Zues, Olga (Washington, DC: World Bank, 2022)
In 2015, the government of Ukraine initiated fundamental reform of its health system with the goals of improving the health outcomes of the population and providing financial protection from excessive out-of-pocket health care payments. This reform was to be implemented through modernizing and integrating the service delivery system, introducing changes to provider payment arrangements that incentivize efficiency, and improving the quality of care. It culminated in the passage of a new health financing law—the Law on Financial Guarantees for Health Care Services 2017—which established a health benefit package called the Program of Medical Guarantees (PMG) and created the National Health Service of Ukraine to serve as the strategic purchaser for this program. Health Financing Reform in Ukraine: Progress and Future Directions provides a comprehensive description and assessment of the development and implementation of policies associated with the PMG reform from the start of the reform in 2017 through mid-2021. It examines (1) how the PMG is financed, (2) strategic purchasing of the different components of the PMG benefit package, and (3) the governance arrangements of the PMG. The report also positions these developments within broader contextual discussions of the financing and organization of health care in Ukraine to make the key features of the financing reforms and their importance accessible to domestic and international audiences.